Wealth and Godliness in Ministry: A Biblical-Theological Analysis of 1 Timothy 6:6–21 - Raulina, Raulina; Gabriel Panjaitan , Geri (Jurnal Didaskalia, 2023)
This article presents a biblical-theological analysis of 1 Timothy 6:6–21 with a focus on the ethical and spiritual challenges posed by wealth in the context of Christian ministry. The study investigates the apostle Paul's exhortation to Timothy concerning godliness, contentment, and the perils of materialism within the early Christian community. Through a close exegetical reading of the text, supported by historical-contextual insights and relevant Greek lexical analysis, the paper explores how the passage delineates the contrast between true spiritual wealth and the corrupting influence of greed. The research highlights Paul's call for ministers to pursue righteousness, faith, love, endurance, and gentleness while maintaining a life free from the love of money. This study contributes to contemporary theological discourse on pastoral integrity, offering critical implications for ethical leadership, especially in ecclesial settings prone to commodification and spiritual compromise.